Digital modeling of the gallbladder for revealing microanatomical features and optimizing surgical approaches in gallbladder-preserving cholelithotomy - Li, Xiangtian; Ye, Xiyin; Yang, Peng; Wu, Haopeng; Fan, Tingyu; Xiao, Zhaoming; Jiang, Qiyang; Lin, Zheyang; Peng, Shasha; Huang, Tingyi; Feng, Xiaohui; Liang, Yuan; et al. (Frontiers in Physiology, 2026)
With the advancement of minimally invasive techniques and the reevaluation of surgical indications, gallbladder-preserving cholecystolithotomy is anticipated to serve as an alternative to cholecystectomy in specific cases. The choice of surgical incision is critical for optimizing gallbladder function preservation, which is a pivotal factor influencing the prognosis of gallbladder-preserving cholecystolithotomy. Consequently, a comprehensive understanding of the distribution of microstructures, including gallbladder blood vessels and nerves, is of substantial significance. For this study, we selected the gallbladders of healthy four-year-old children as our subjects. Gallbladder specimens were dehydrated, paraffin-embedded, and serially sectioned into hundreds of 4-μm-thick slices. Sections were selectively stained with distinct protocols—hematoxylin and eosin (H&E) and anti-tyrosine hydroxylase immunohistochemical staining—followed by sequential numbering. Digitized sections were reconstructed into three-dimensional models (3D) using computational software. The resultant 3D gallbladder models achieved a resolution threshold of <20 μm, enabling visualization of microvascular and neural structures. Independent and integrated analyses of the modeled cystic arteries, veins, and sympathetic neural networks revealed two superficial arterial trunks and one deep branch originating from the superficial division of the cystic artery, with their interactive patterns defining nutrient-supplying territories. Further mapping of microvascular and neural trajectories within the digital models identified a minimally function-disruptive surgical incision site, diverging from conventional fundal incision approaches for gallstone extraction. This approach offers a 3D visualization framework to enhance pathological slice interpretation—thereby facilitating histopathological diagnosis—and is proposed as a novel surgical route for gallbladder-preserving cholelithotomy.